Change in Scenario of Foreign Investment in India (From 20th to 21st Century) - Ghai, Shyam Kumar (Journal of Commerce and Trade, 2015)
The broad thrust of the new policies is not very different from the changes being implemented in other developing countries and also all over the erstwhile socialist world. They aim at reducing the extent of Government controls over various aspects of the domestic economy, increasing the role of the private sector, redirecting scarce public sector resources to areas where the private sector is unlikely to enter, and opening up the economy to trade and foreign investment. So far as other modes of investment in India are concerned, these are equally imperative in order to understand various strategies / steps taken towards path of success achievement by India. Thus, the knowledge of these other important aspects, especially various rules & regulations framed along with FDI, becomes imperative in order to get better picture of economic reforms. Ultimately, the combined efforts of DI & PI produced an increasing trend of Rs. 14,808 crore per annum. After initial negative results for five years, it is expected to touch Rs. 436,458 crore by 2024-25, which is a good sign. Thus, the present paper depicts that the World is looking towards India inspite of all ups and downs (the second largest populated country) as secure and fruitful investment avenue. Things would definitely take better shape, if potholes in the path of progress are timely taken care of.